2018
DOI: 10.3390/brainsci8050093
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Enhancement of Axon Regeneration Following Peripheral Nerve Injury in the SLICK-A Mouse

Abstract: The effects of chemogenetics on axon regeneration following peripheral nerve transection and repair were studied in mice expressing a Cre-dependent excitatory designer receptor exclusively activated by designer drugs (DREADD) and Cre-recombinase/yellow fluorescent protein (YFP) in a subset of motor and sensory neurons and cortical motoneurons (SLICK-A). Sciatic nerves were cut and repaired and mice were treated either once, at the time of injury, or five days per week for two weeks with clozapine N-oxide (CNO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…2 weeks) following sciatic nerve injury resulted in greater axon regeneration than a single activation 67 . However, continuous electrical stimulation for 2 weeks does not 68 .…”
Section: Discussionmentioning
confidence: 90%
“…2 weeks) following sciatic nerve injury resulted in greater axon regeneration than a single activation 67 . However, continuous electrical stimulation for 2 weeks does not 68 .…”
Section: Discussionmentioning
confidence: 90%
“…By comparing EMG response amplitudes in the same latency windows over a range of stimulus intensities (optical or electrical), a full motor recruitment curve can be generated (Figure 5B) and the stimulus threshold for activation and maximal evoked responses can be determined. If a change in neuronal excitability is expected, such as when using an inhibitory opsin (Jaiswal et al , 2018), such an effect can be evaluated as changes in stimulus threshold. Using recording electrodes placed on the nerve, optical nerve stimulation can be used to collect an evoked electroneurogram (Ward et al , 2018) and similar quantitative measurements can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Future advances in excitatory and inhibitory opsins, bioluminescence, luminopsins and chemogenetics will continue to facilitate the development of neuromodulation and novel gene therapy approaches. Via chemogenetic manipulation using DREADDs (Cre-dependent excitatory designer receptor exclusively activated by designer drugs), we have shown that subthreshold excitation of motoneurons and sensory neurons is sufficient to enhance their regeneration (Jaiswal et al , 2018). The application of these new optogenetic tools will expand our ability to further define the activity requirements of highly specific neuronal populations.…”
Section: [Background]mentioning
confidence: 99%
“…Enhancement of regeneration of axons of many more motoneurons than are likely to be brought into full activity is found after treatments with exercise at a slow treadmill speed (Gordon and English, 2016). Simply increasing the excitability of injured neurons using chemogenetics could be sufficient to enhance regeneration (Jaiswal et al, 2018).…”
Section: Mechanismsmentioning
confidence: 99%